FACTORS INFLUENCING ENVIRONMENTAL DISCLOSURE IN CONSUMER GOODS INDUSTRY AND MINING COMPANIES - Purwanto, Adelia Puspita; Nugroho, Paskah Ika (International Journal of Social Science and Business, 2020)
This study evaluates the influence of environmental performance, profitability, firm size, and leverage on environmental disclosure. This research is replicated from Dewi and Yasa?s research on 2017, with some modifications. The population collected from the annual report and/or sustainability report of consumer goods industry and mining companies listed in Indonesia Stock Exchange (IDX) and PROPER or Program Penilaian Peringkat Kinerja Perusahaan in 2017 until 2018. The technique of take the sample was purposive sampling and the total of 56 data was being the samples in this study. The result of the statistical tests prove that profitability and firm size have positively associate and influence to environmental disclosure. Meanwhile, environmental performance and leverage were insignificantly influence to environmental disclosure. This research also found that some of the companies that being tested still have less awareness in exposing their environmental disclosure.